2001
DOI: 10.1348/026151001166010
|View full text |Cite
|
Sign up to set email alerts
|

Attachment‐based intervention in adoptive families in infancy and children's development at age 7: Two follow‐up studies

Abstract: In the present study we examined the longitudinal effects of an early attachmentbased intervention on children's social development, personality development, and incidence of behaviour problems at age 7. The behaviourally focused intervention was carried out in families with internationally, transracially adopted children placed before 6 months of age. The intervention was implemented during the child's first year of life in mixed families (i.e. adoptive families with biological children) and in all‐adoptive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 0 publications
5
36
1
4
Order By: Relevance
“…Similarly, three articles (Juffer et al, 1997(Juffer et al, , 2005Stams et al, 2001) were found to be follow-ups of the same sample and are therefore also considered here as one study. In total, ten studies (13 articles) were included in the review.…”
Section: Database Searchesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, three articles (Juffer et al, 1997(Juffer et al, , 2005Stams et al, 2001) were found to be follow-ups of the same sample and are therefore also considered here as one study. In total, ten studies (13 articles) were included in the review.…”
Section: Database Searchesmentioning
confidence: 99%
“…Two studies (Dozier et al, 2006(Dozier et al, , 2009Juffer et al, 1997, 2005/Stams et al, 2001 included infants who were not reported to be displaying any difficulties, but were considered to be at high risk for future difficulties. In the sample in Dozier et al (2006Dozier et al ( , 2009, infants were recruited at the start of initial foster care placement, while in Juffer et al, (1997, 2005)/Stam et al's (2001 sample, internationally adopted infants at six months of age were followed up over seven years.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also reveal a greater percentage of adopted children classified as disorganized in the Strange Situation Test (e.g., Dozier, Stoval, Albus, and Bates, 2001;Marcovitch et al, 1997). Studies of trans-racial and international adoptions have also raised questions and concerns about attachment formation (e.g., Chisholm, 1998; O'Connor, Rutter, & The English and Romanian Adoptees Study Team, 2000;Smyke, Dumitrescu, & Zeanah, 2002;Stams, Juffer, van IJzendoorn, & Hoksbergen, 2001;Zeneah, 2000). However, most of these studies focused on children adopted after their first year or from severely depriving environments, conditions that seem likely to increase the incidence of insecure attachment relationships.…”
mentioning
confidence: 99%
“…Ego sağlamlığı, sosyal yetkinlik (Block ve Block, 2006), içselleştirme ve dışsallaştırma problemleri (Eisenberg vd., 1996;Hofer, Eisenberg ve Reiser, 2010) ile zihinsel ve dikkatsel fonksiyonlarla (Martel vd., 2007) ilgilidir. Bazı bireysel (Eisenberg vd., 2004;Eisenberg, Spinrad ve Morris, 2002), ailesel (Stams, Juffer, van IJzendoorn ve Hocksbergen, 2001) ve çevresel (Masten ve Coatsworth, 1998) faktörlerin ego sağlamlığı ile ilişkili olduğu görülmektedir.…”
Section: Introductionunclassified